2022
DOI: 10.3390/en15176300
|View full text |Cite
|
Sign up to set email alerts
|

Intentions to Use Prosumer Photovoltaic Technology in Poland

Abstract: The energy transition that Poland is facing directs investment and research efforts towards renewable energy sources (RES). This topic has gained importance due to environmental and climate reasons and, recently, the ongoing military conflict between Russia and Ukraine. All these issues affect the availability and prices of fossil fuels, on which electricity production in Poland currently depends. Therefore, to change the current state of affairs, it is necessary to turn to other sources of energy, including R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…the main reason for the low popularity is the principle of mandatory balancing by the system of energy injected by the prosumer until 2023 (net metering principle). The change of this rule to net billing in 2023, as well as subsidies for the purchase of energy storage under the next "My Electricity" program, may change prosumers' approach to investing in their storage [8,9]. according to the authors, such a distributed system can, without significant grid investments, considerably flatten the daily curve of electricity demand in the system.…”
Section: • Energy Storagementioning
confidence: 99%
“…the main reason for the low popularity is the principle of mandatory balancing by the system of energy injected by the prosumer until 2023 (net metering principle). The change of this rule to net billing in 2023, as well as subsidies for the purchase of energy storage under the next "My Electricity" program, may change prosumers' approach to investing in their storage [8,9]. according to the authors, such a distributed system can, without significant grid investments, considerably flatten the daily curve of electricity demand in the system.…”
Section: • Energy Storagementioning
confidence: 99%
“…[ 45 ] explored the influencing factors of DPV development in Argentina, and the results indicated that environmental factors such as political instability, energy subsidies, and high inflation rates were considered as the primary obstacles. [ 46 ] conducted a questionnaire survey involving 430 participants in Poland and found that factors influencing consumers’ attitudes towards PV technology are related to environmental concerns, economic factors, and factors associated with the usability of PV technology. [ 47 ] conducted a survey involving 20 experts and 29 electricity consumers and found that consumers primarily focus on generation capacity, electricity costs, photovoltaic system costs, and financial capability when adopting distributed photovoltaic electricity generation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research to date also shows that decisions on the use of photovoltaics are made mainly on the basis of attitudes to solar energy, and the factors promoting this RES are of much less importance [63]. In addition, government programs subsidizing the use of solar energy are very well received by enthusiasts of such a solution, despite the fact that they see the high costs of such an investment and the lack of energy storage systems.…”
Section: The Use Of Solar Energy In Emerging and Developing Economiesmentioning
confidence: 99%